1998
DOI: 10.1159/000009974
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Outcome of Oligohydramnios without Associated Premature Rupture of Membranes and Fetal Anomalies

Abstract: To investigate the perinatal outcome of patients with oligohydramnios (amniotic fluid index ≤5 cm), but without premature rupture of membranes and fetal congenital anomalies, data from 245 singleton pregnancies were analyzed and compared to those with normal amniotic fluid volumes (5 < amniotic fluid index < 24 cm, n = 27,261). Significantly higher incidences of primiparity, pregnancy-induced hypertension, premature separation of placenta, past history of intrauterine fetal death, past history of preterm deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 14 publications
3
22
0
Order By: Relevance
“…The incidence was influenced by the population studied and the gestational age at the time of the ultrasound examination. In this study, the incidence of oligohydramnios was 0.89% (5,228/584,653), which was similar to the incidence (0.88%) reported between 1990 and 1996 in Taiwan (17). Previous studies have reported the short-term outcomes of pregnancies complicated by oligohydramnios (9-12).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The incidence was influenced by the population studied and the gestational age at the time of the ultrasound examination. In this study, the incidence of oligohydramnios was 0.89% (5,228/584,653), which was similar to the incidence (0.88%) reported between 1990 and 1996 in Taiwan (17). Previous studies have reported the short-term outcomes of pregnancies complicated by oligohydramnios (9-12).…”
Section: Discussionsupporting
confidence: 85%
“…Cases were selected if women had a diagnosis of oligohydramnios (ICD-9-CM: 658.0) in the third trimester of pregnancy, according to inpatient or outpatient claims. Ultrasonography is widely used in Taiwan to diagnose oligohydramnios during prenatal care because the amniotic fluid index is less than 5 cm (17). During a normal pregnancy, the amount of amniotic fluid typically increases until the sixth month and then slightly decreases during the eighth and ninth months (34).…”
Section: Patient Selectionmentioning
confidence: 99%
“…[1][2][3][4][5] In addition to fetal urologic anomalies, such as renal agenesis or urethral obstruction, and rupture of membranes, oligohydramnios can be caused by uteroplacental insufficiency. Maternal diseases that cause vascular injury such as chronic hypertension, pregestational diabetes mellitus, and collagen vascular diseases are associated with decreased fetal renal perfusion, as are medications such as indomethacin, which inhibits formation of prostacyclin and PGE 2 , leading to decreased fetal renal blood flow and decreased fetal urine production.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that oligohydramnios is a risk factor for the outcome of pregnancy, causing in many cases meconium staining, umbilical cord compression, fetal heart rate alterations, increased rate of cesarean section and other complications [2][3][4][5]. Amniotic fluid volume is a biophysical parameter with particular significance in high-risk pregnancies [6].…”
Section: Introductionmentioning
confidence: 99%